Natural hazards and wildlife health: The effects of a volcanic eruption on the Andean Condor. (23rd November 2019) - Plaza, Pablo I; Wiemeyer, Guillermo; Blanco, Guillermo; Alarcón, Pablo; Hornero-Méndez, Dámaso; Donázar, José Antonio; Sánchez-Zapata, José Antonio; Hiraldo, Fernando; de la Rosa, Jesús; Lambertucci, Sergio A
Abstract: Volcanic eruptions produce health changes in animals that may be associated with emitted gases and deposited ashes. We evaluated whether the Puyehue–Cordón Caulle volcanic eruption in 2011 produced health changes in the threatened Andean Condor ( Vultur gryphus ) living in the area most affected by the eruption, northwestern Patagonia. We studied clinical and biochemical parameters of condors examined before and after the eruption. We also examined concentrations of different metals and metalloids in the blood of individuals sampled after the eruption. The most common clinical abnormality associated with the eruptive process was irritating pharyngitis. In condors sampled after the eruption, blood concentrations of albumin, calcium, carotenoids, and total proteins decreased to levels under the reference values reported for this species. We found different chemical elements in the blood of these condors after the eruption, such as arsenic and cadmium, with the potential to produce health impacts. Thus, the health of Andean Condors was affected in different ways by the eruption; remaining in the affected area appears to have been costly. However, in comparison to other animal species, the health impacts were not as strong and were mainly related to food shortages due to the decrease in availability of livestock carcasses linked to the eruption. This suggests that condors dealt relatively well with this massive event. Future research is needed to evaluate if the health changes we found reduce the survival of this species, and if the cost of inhabiting volcanic areas has any ecological or evolutionary influence on the condor's life history.